The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1088/0953-4075/37/12/007
|View full text |Cite
|
Sign up to set email alerts
|

Elastic scattering of photon by the Ne atom and the Ne6+ion

Abstract: A theoretical study has been performed on the absolute values and the shapes of the differential cross sections of the elastic scattering of an x-ray photon by the Ne atom and by its Be-like ion Ne 6+ near the 1s-shell ionization threshold. The results of calculations for the Ne atom were found to be in agreement with the high-precision synchrotron radiation experiment by Coreno et al (1999 Phys. Rev. A 59 2494. The results of calculations for the Ne 6+ ion are predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…3-5 the violation of equality (16) leads to the loss of scattering intensity in the region of energies co0 ^ / ls. In our other work [12] it is shown that for the Ne atom, a similar Top solid curve: sum of functions pn, T)s = 0.24 eV [5]; (b) r ls = 0.27 eV [6]. I\s = 868.39 eV (calculation of this work), io0 is energy of the photon preparing the ls2s22p6(n,e)p initial scattering states.…”
Section: Theorysupporting
confidence: 56%
“…3-5 the violation of equality (16) leads to the loss of scattering intensity in the region of energies co0 ^ / ls. In our other work [12] it is shown that for the Ne atom, a similar Top solid curve: sum of functions pn, T)s = 0.24 eV [5]; (b) r ls = 0.27 eV [6]. I\s = 868.39 eV (calculation of this work), io0 is energy of the photon preparing the ls2s22p6(n,e)p initial scattering states.…”
Section: Theorysupporting
confidence: 56%
“…In the case of m from k 3 to ∞, the summation over the virtual one-electron mp-states excitation is performed analytically by the methods of work by Hopersky et al (2004) in the frame of the quasi-classical quantum-mechanical approximation for single and highly excited states m from k F (F is the Fermi level or the set of the quantum numbers of the valence shell of an atom (ion)) to ∞ (see, for example, Bethe (1964)):…”
Section: Results Of the Calculationsmentioning
confidence: 99%